Essentially Equivalent to a Dividend (Book). - Dunham, Clive F. (The Accounting Review, 1961)
Reviews the book "Essentially Equivalent to a Dividend," by Paul D. Seghers, William J. Reinhart and Selwyn Nimaroff.